ADAR, the carcinogenesis mechanisms of ADAR and related clinical applications - Zhang, Yue (Ann Transl Med, 2019)
Adenosine deaminases acting on RNA (ADARs) catalyze the conversion of adenosine (A) to inosine (I) in double-stranded RNA, which can change the codons after transcription. Abnormal ADAR editing is present in a variety of cancers. However, the study of the biological effects of ADARs in cancer is not very deep. Here, we review current important ADAR-mediated editing events, related carcinogenic mechanisms and applications in clinical medicine. Further exploration in ADARs can provide a new direction for cancer treatment.